Sequential therapy from entecavir to tenofovir alafenamide versus continuous entecavir monotherapy for patients with chronic hepatitis B - Itokawa, Norio (JGH Open, 2020)
BACKGROUND AND AIM: Although tenofovir alafenamide (TAF), as well as entecavir (ETV), is widely used as first‐line treatment for patients with chronic hepatitis B, there are only a few studies comparing sequential therapy from ETV to TAF and continuous ETV monotherapy in patients with maintained virologic response to ETV. METHODS: In a retrospective multicenter study, we investigated the efficacy and safety of sequential therapy from ETV to TAF (ETV‐TAF group) and compared them with continuous ETV monotherapy (ETV group), using propensity score matching, in chronic hepatitis B patients. RESULTS: From 442 patients, we analyzed 142 patients from each group comprising 71 patients matched for several data, including age, HBV genotype, hepatitis B envelope antigen, cirrhosis, alanine aminotransferase, platelet count, prior ETV monotherapy period, and hepatitis B surface antigen (HBsAg) change during prior ETV monotherapy. In the ETV‐TAF group, HBsAg levels significantly decreased from baseline to 48 weeks after switching to TAF (−0.02 log IU/mL, P = 0.038). HBcrAg levels also significantly decreased after switching to TAF (−0.1 log IU/mL, P = 0.004). However, there were no significant differences in the reduction of HBsAg and HBcrAg levels between the ETV‐TAF and ETV groups. There was no significant difference in the change of estimated glomerular filtration rate levels from baseline to 48 weeks between the two groups. CONCLUSIONS: The present study indicated that the efficacy, especially of the HBsAg‐reducing action, and safety of sequential therapy from ETV to TAF were similar to those of continuous ETV monotherapy among chronic hepatitis B patients with maintained virologic response to ETV.